Control of a three-stage medium voltage solid-state transformer - Busada, Claudio (2017)
This paper proposes the modeling and control of a Solid-State Transformer using a three-stage conversion topology. First, a rectification stage is used, where a three-phase high-voltage AC signal is converted to a DC level; this stage is then followed by a DC-DC converter, and finally an inverter is used to convert the DC into a three-phase low-voltage AC signal. The adopted topology is modeled using a simplified model for each stage, useful to design their controllers. Based on these models, the controllers are tuned to obtain a good performance to sudden load changes. This performance is tested through simulations.